Relevansi Nilai – Nilai Nasionalisme dan Potret Masyarakat di Daerah Perbatasan Republik Indonesia – Republik Demokratik Timor Leste (Studi Kasus Desa Napan, Kecamatan Bikomi Utara, Kabupaten Timor Tengah Utara, Provinsi Nusa Tenggara Timur) - Feka, Yanuarius Sani; F. Anin, Helidorus (Universitas Muhammadiyah Ponorogo, 2023)
Indonesian nationalism in border areas often has social issues or conflicts. Strengthening human resources, development or pluralistic primordial character is important in implementing the values of nationalism so that it is relevant to what the Indonesian nation aspires to be. Weak people's behavior towards the value of nationalism will make people become apathetic due to the fading nature of nationalism due to the ineffectiveness of instilling the values of nationalism in the community. The study of the relevance of border communities to the values of nationalism is needed as a character building for the face of the border which relates to human attitudes and behavior, as well as the living conditions of the research area as a border area as well as the benefits of seeing people's behavior in interpreting life in building the nation and loyalty to the state. The nation's journey is often faced with various phenomena of the emergence of other ideologies, so the role of society and the government is to preserve the value of nationalism as something that is absolute for realizing the ideals of the state. TheÂ development of the value of nationalism depends on how the citizens' national way of thinking is applied, because it will not work without the spirit of nationalism from the people themselves. The value of nationalism has the goal of teaching a sense of love for the nation and state as well as public awareness in maintaining and perpetuating the identity, integrity, prosperity and strength of the nation. This study uses a qualitative approach with the techniques used to collect data in this research observation, interview and documentation techniques. The results of the research describe that the border community sees nationalism as a matter of development in physical form. The relevance that has been ingrained in the culture of the border community is the value of respecting differences and mutual cooperation. strengthening human resources, development or pluralistic primordial character. It is important to implement the values of nationalism so that it is relevant to what the Indonesian nation aspires to be. Border areas provide a view as a means of upholding the territorial sovereignty of the Republic of Indonesia against all forms of threats both from outside and from within the country.